Methods of Dietary Sodium Estimation - P. Aparna; Harshal Ramesh Salve; Anand Krishnan; Ramakrishnan Lakshmy; Sanjeev Kumar Gupta; Baridalyne Nongkynrih (Indian Journal of Medical Specialities)
Excessive dietary sodium intake is found to be associated with high blood pressure and its consequences such as cardiovascular disease and stroke. Daily sodium intake is found to vary from place to place as it is dependent on geography, ethnicity, socioeconomic factors, etc. In this review, we summarize the various methods of assessment of daily sodium intake such as dietary estimation methods using 24-h dietary recall, food frequency questionnaire and diet record, and biochemical methods using 24-h urine sodium or spot urine sodium estimation. Daily sodium intake estimated with spot urine sodium is dependent on the equation used to convert spot urine sodium to 24-h urine sodium. To identify the appropriate equation, validation studies need to be conducted. Population level sodium intake and it's monitoring is important for reduction of noncommunicable diseases.